2022
DOI: 10.3389/fpubh.2022.814112
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Household Food Security in Urban and Peri-Urban Areas of Hyderabad, India

Abstract: This paper investigates the impact of the COVID-19 pandemic on food security and on coping-strategies in urban and peri-urban areas of the Hyderabad, India. Household survey data were collected before (October 2018) and during (January 2021) the onset of the pandemic. Results from logistic regression with the standarized Food Insecurity Expecience Scale (FIES) as dependent variable reveal that close to 40% of the households surveyed experienced a deterioration in food security status during the pandemic. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…These results helped to identify vulnerable populations during the pandemic. Similar findings were found in other Asia-Pacific countries [ 19 20 21 ]. Many reports pointed out that women were more vulnerable to losing their jobs and income due to economic recession during the pandemic than men in the UK, US, and Germany [ 22 ] and were at higher risk of food security across regions.…”
Section: Discussionsupporting
confidence: 90%
“…These results helped to identify vulnerable populations during the pandemic. Similar findings were found in other Asia-Pacific countries [ 19 20 21 ]. Many reports pointed out that women were more vulnerable to losing their jobs and income due to economic recession during the pandemic than men in the UK, US, and Germany [ 22 ] and were at higher risk of food security across regions.…”
Section: Discussionsupporting
confidence: 90%
“…Studies suggest that COVID-19 has disrupted the global food system in a number of ways, including trade restrictions, supply chain disruptions, and reduced access to markets and labor (Kubatko et al 2023). Local food, the food produced locally through community gardens, backyard gardens, and local farms, is promising to enhance the food system resilience (Padmaja et al 2022). Our survey also found that many respondents (79 percent) considered local food a critical component of the food system.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wertheim-Heck et al (14) food and nutrition insecurity is widely recognised among metropolitan Asia's low-income populations. During the COVID-19 pandemic, highly populated, economically challenged metropolitan areas were impacted the hardest (15).…”
Section: Discussionmentioning
confidence: 99%